Analysis of Village Facilitators Permormances in Bone Raya Sub-District of Bone Bolango Regency - Rahna Juwita Hatta Era; Sri Yulianty Mozin; William Indra S.Mooduto (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The purposes of this research are: 1) to understand and to analyze the performances of village facilitators in implementing government policies on community empowerment; 2) to describe the inhabiting factors of village facilitators to assist the villages in Bone Raya Sub- District. This is a descriptive research as the problem solving investigated by describing/ portraying current state of the object/subject of research based on the fact that appear as they are. The result of research shows that: 1) the performance of village facilitators both in terms of Performances supervsion in the program stages is well running in tiered with the amplifying of village government, Village Council (BPD) by socializing the latest regulation; 2) Performances Supervising, there are a lot to be addressed especially in identifying weakness of the institution, facilitators have to directly interact with the institution not based on the presence in the village meeting; 3)Village facilitators in 2020 carriied out stages coordination wihout violeting the code of ethics as facilitators in an effective team work; 4) adminitrative performances of the village facilitators in 2020 is good but there is a delay in sending the data report at the village level to the regency level caused by the uneffective time management to request the data to the village government; 5) the inhabiting factor village facilitators performances is the unachieved work quality because it depends on the village chief policies which doesn’t comply with teh regulations submitted by village facilitators. In addition, unpunctuality in facilitating the village due to the distance of residence and the number of villages that had not yet developed a good work commmitment due to teh frequent late siging of contracts.